1982
DOI: 10.1042/bj2040525
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the membrane proteins of rat liver lysosomes. Composition, enzyme activities and turnover

Abstract: Lysosomes prepared from the livers of untreated rats and from the livers of rats injected with either Triton WR-1339 or dextran yielded membranes that were similar in both polypeptide composition and activities of ATPase and acid 5'-nucleotidase. The administration of Triton WR-1339 (and dextran) resulted in an increase in ATPase activity of liver homogenates that was associated with a parallel increase in the ATPase activity of the lysosomal membrane. On the other hand, plasma membranes appear to be different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…2A) is an example of potential cross-contamination. Lysosomes are quite fragile, a characteristic that is noted and/or exploited in traditional fractionation methods (Burnside and Schneider, 1982;Ohsumi et al, 1983); therefore, it is likely that a portion of the lysosomes were disrupted during the homogenization process in both SCH and whole-tissue matrices. 2) Potential disruption of binding equilibrium between cellular compartments occurs during the fractionation process.…”
Section: Discussionmentioning
confidence: 99%
“…2A) is an example of potential cross-contamination. Lysosomes are quite fragile, a characteristic that is noted and/or exploited in traditional fractionation methods (Burnside and Schneider, 1982;Ohsumi et al, 1983); therefore, it is likely that a portion of the lysosomes were disrupted during the homogenization process in both SCH and whole-tissue matrices. 2) Potential disruption of binding equilibrium between cellular compartments occurs during the fractionation process.…”
Section: Discussionmentioning
confidence: 99%
“…While many procedures have been used for lysosomal purification, we chose one of the most reliable and best studied, namely, Triton WR1339-filled rat liver lysosomes (tritosomes) as described by Leighton et al (12). Although tritosomes are considered modified lysosomes as they contain a quantity of non-physiological material (Triton WR1339), tritosomes retain lysosomal enzymatic activities (6,(12)(13)(14) and perform identically to lysosomes in endosomal and phagosomal fusion assays (15). In this study we identified 215 separate proteins in the integral membrane protein fraction of the lysosome, many not previously associated with the lysosome and several that are still only identified as uncharacterized cDNAs.…”
mentioning
confidence: 87%
“…have been extensively characterized as functional secondary (late stage) lysosomes (12,14,15,19). We have previously demonstrated the enrichment of lysosomal markers (␤-hexosaminidase activity, Rab7, and LAMP-1) in our tritosome preparations (70-fold enrichment of ␤-hexosaminidase) and the absence of markers from mitochondria (citrate synthase activity) and ER (calnexin protein) (Refs.…”
Section: Triton Wr1339-filled Lysosomes (Tritosomes)-tritosomesmentioning
confidence: 99%
“…Tritosomes are lysosomes that have ingested Triton. They are a wellestablished model of rat liver lysosomes distinct from early endosomes, late endosomes, and phagosomes, as previously shown by electron microscopy, enzyme assays, Western blots of marker proteins, and phagosome-fusion assays (Leighton et al, 1968;Khan et al, 1981;Burnside & Schneider, 1982;Wattiaux et al, 1996). Briefly, Tritosomes are obtained by injecting Triton WR1339 (Tyloxapol) to rats 5 days prior to sacrifice.…”
Section: Proteomic Studies Of Lysosomes and Breast Cancermentioning
confidence: 99%